FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ivan Lemmuel; Ida Bagus Nyoman Sukadana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research to test factors affecting tax aggresiveness in registered manufacturing companies on Indonesian Stock Exchange (IDX). The variable used in the company are capital intensity, inventory intensity, profitability, leverage, liquidity, independent commisionarer, audit quality.Population of this research is manufactured companies which are listed in Indonesia Stock Exchange from 2017 to 2019. The sample of this research are selected by using purposive sampling method, and 240 datas are taken. Data were analyzed using multiple regression method. The result of this research shows that inventory intensity, profitability, leverage have influence to aggressiveness tax, whereas capital intensity, liquidity, independent commisionarer, audit quality do not have influence to aggressiveness tax.